Lagos’ Vulnerability to Flood’s Changes Mapping Adopting Analytical Hierarchy Process Using Geographical Information System - Uwadiegwu Ibeabuchi (International Journal Labs, 2023)
Flood disaster is considered a major natural hazard plaguing Lagosains due to its devastating effect on affected communities. Analytical Hierarchy Process (AHP) was adopted using Geographical Information System (GIS) to determine areas vulnerable to flood in Lagos for 1984 and 2013. This research considers the contribution of rainfall, elevation, land use, slope and soil to flood. AHP method was applied to these factors by means of ranking and pairwise comparison. This products a relative weight of 34.45% for slope, 19.58% for rainfall, 18.79% for land use, 18.61% for elevation, and 8.57% for soil. The consistency value was found to be reasonable with a consistency index of 0.0738 with a consistency ratio of 7%, these aids in flood vulnerability mapping. This reveals that the impact of flood is high for residential and socio-economic activities in Lagos, thus, this will assist decision makers on the menace posed by the disaster and mitigation measures to adopt.